Thermogravimetric Analysis Of The Complex Compound Formed By 4- Nitrophenylacetic Acid With Ce Ion - Rasulova S.M; Toshboltaeva Kh.A; Turaev Kh.Kh; Ibragimov A.B (Genius Journals, 2025)
4-Nitrophenylacetic acid (4-NPA), belonging to the class of nitroaromatic acids, is one of the important intermediate compounds widely studied in the fields of pharmaceuticals, coordination chemistry, materials science, and biochemistry. Its molecule simultaneously contains an electron-accepting nitro group (-NO2) and an aromatic ring bonded with an acidic carboxyl group (-COOH) and a methylene group (-CH2-). This structure forms the basis for its manifestation as a compound with diverse physicochemical, complexing, and biologically active properties. This article summarizes the physicochemical, structural, and biological properties of 4-nitrophenylacetic acid based on various literary sources, providing a comprehensive analysis of their interrelationships, potential applications, and chemical reactivity
Keywords: 4-NPA 4-nitrophenylacetic acid; Apelblat; NRTL; crystallization reaction